Animal in Indian art : catalogue of the exhibition held at the Prince of Wales Museum of Western India, Bombay from 30 September to 21 October 1977 - Gorakshkar, Sadashiv, 1933- (S. Gorakshkar, Director, on behalf of the Board of Trustees of the Museum, 1979)
Articles and pictoral representation.